Staying Alive! Entrepreneurial Human Capital and Resilience of New Ventures - Braunerhjelm, Pontus; Lappi, Emma (Organization Science, 2026)
Survival of new ventures has been shown to exhibit considerable heterogeneity both across and within industries. Some of the explanations for these differences have been attributed to firm size, organizational structure, and management practices. We add to this literature by showing how differences in employees’ abilities and their knowledge domain relate to survival. More precisely, we focus on the role of employees who in the past started and managed firms, referred to as an organization’s entrepreneurial human capital (EHC). Theoretically, we adopt an eclectic approach, while the empirical analysis is based on longitudinal register data for Sweden from 1997 to 2016. This allows us to identify EHC for all new ventures over the past 20 years. After controlling for a large number of confounders, our baseline results strongly suggest that a higher share of employees with entrepreneurial backgrounds is associated with an increased probability of new venture survival. We identify the following mechanisms through which former entrepreneurs contribute to survival: an enlarged resource base, magnified by learning from longer spells in entrepreneurship; an organizational fit conducive to absorbing and utilizing EHC; and a human capital fit in which entrepreneurial competencies align with the competence requirements of new ventures. We argue that our findings have both theoretical and practical implications for recruiters and managers and provide valuable insights for policymakers.